Exploring the Architectural-identity of Bali Post Hasta Kosala Kosali - Maha Putra, I Nyoman Gede (Universitas Pendidikan Indonesia, 2019)
As the product of culture and the background of human activities, architecture that constructs place-identity are in a state of constant modification. This paper explores the dynamic development of architecture of a vernacular landscape since the time when external power of colonialization introduced new ideas, techniques and construction methods to the more traditional know how. A case study in Bali is analyzed through historical research involving document and policy analysis, in depth interview with key informants, observation and building surveys. The result shows that prior to colonization era, the island was developed based on local building codes called Hasta Kosala-Kosali that is written on traditional lontar leaf manuscripts. New political system as well as business interests are two main factors influencing the transformation of architectural-identity of the island in the colonial and post-colonial era to date. The physical identity is among the main charms of the Island of Bali. In order to maintain the attractiveness of the island, the public and private sector should work together with the community in establishing policies regarding the physical development of Bali.Keywords: Architectural identity, tradition, post-colonialism, hasta kosala-kosali